ANALISIS USAHA AGROINDUSTRI DAN MARKETING MIX PADA USAHA TAHU DI DESA AIR TAWAR KECAMATAN KATEMAN KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - Rafika Putri Aulia; Fahrial (DINAMIKA PERTANIAN, 2024)
Tofu products are in high demand, but there is a shortage of raw materials to satisfy business requirements, posing challenges for entrepreneurs. This study intends to analyze (1) the characteristics of stakeholders (entrepreneurs, workers, traders, and customers) and the business profile of the tofu agroindustry; (2) the aspects of the tofu agroindustry business (including raw materials, supporting materials, production technology, processes, costs, selling prices, income, efficiency, and added value); and (3) the marketing mix utilized in the agroindustry business. The research was conducted using a survey method in Air Tawar Village, Kateman District, Indragiri Hilir Regency, from February to July 2023. Both quantitative and qualitative data were collected using Hayami and Likert scale methodologies. The findings indicate that (1) entrepreneurs are of productive age, have an average education level of 9 years, possess 14 years of business experience, and have an average of four family members. The workforce is predominantly of productive age, with an average education level of 7 years, 2.5 years of business experience, and two family dependents. Traders and customers typically have an average age of 42 and 40 years, an education level of 12 years, 11 years of business experience, and an average family size of four. This tofu business has been operational for 14 years on a micro scale, supported by equity capital, and employs four workers. (2) The raw material used is primarily soybeans, along with ingredients such as vinegar and water, and other inputs including diesel, firewood, and plastic wrapping. Monthly production costs are IDR 57,468,000, yielding a production output of 14,175 kg of tofu per month, with a selling price of IDR 11,000/kg. The gross monthly income is IDR 155,925,000, resulting in a net income of IDR 72,891,719. The business efficiency ratio stands at 1.88, with added value calculated at IDR 25,855/kg and a profit margin of 86.03%. (3) The marketing strategy for tofu products employs a 7P marketing mix framework specific to the agroindustry, encompassing product, price, promotion, place, people, process, and physical evidence for traders and customers. Entrepreneurs have also received feedback on various aspects, including product, promotion, place, and process, to inform their future strategies.